Cloning and sequence analysis of orchids CymMV and ORSV CP gene isolated in northern of Vietnam - Minh Hang, Nguyen Thi; Thang, Bui Van; Ngoc, Pham Bich; Ha, Chu Hoang (Academia Journal of Biology, 2013)
Orchids are ones of indoor decorated plants with beautiful and fragrant flowers. It is not only varied in styles, but also high economic valuable flower. However, the cultivation of orchids meets several difficulties, especially viral infection that caused reducing the productivity and quality of orchid flowers. Cymbidium mosaic virus (CymMV) and Odontoglossum ringspot tobamo virus (ORSV) are considered as viruses that cause the largest damage to orchids. In this study, we cloned and sequenced the coating protein genes (CP) of the two viruses CymMV and ORSV isolated from some provinces in northern Vietnam. These sequences were aligned out by BioEdit 7 software. The CP nucleotide sequences of the isolates were compared with those of previously published isolates in GenBank originating from different countries. The results showed the CP gene sequences of CymMV were quite diverse, in contrast, the CP genes of ORSV were very conservative. These results contributed to the study of genetic diversity of the CymMV and ORSV viruses and as a basis for selection genetic materials to create disease resistant orchids in Vietnam.